2013
DOI: 10.4193/rhino12.139
|View full text |Cite
|
Sign up to set email alerts
|

Does airway integrated nasal packing after septal surgery improve body oxygenation?

Abstract: Background: Airway integrated nasal packing reportedly improves body oxygenation after septal surgery. This randomized controlled study examined the effect of airway integrated nasal packing on oxygen saturation. Methods: Eighty patients with septal deviation and hypertrophic turbinate were randomly divided into two groups: Group 1 patients were postoperatively packed with airway integrated Nasopore, and Group 2 patients were postoperatively packed with Nasopore without airway integration. The haemodynamic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Interestingly, Yu et al, in their study revealed notable differences in postoperative pain reduction between the two groups. 15 Patients in Group-2, who received Nasopore packing without an integrated airway, reported lower pain scores compared to Group-1 patients, who received Nasopore packing with an integrated airway. This discrepancy suggests that the presence of the integrated airway may have compromised the softness of the packing material.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Interestingly, Yu et al, in their study revealed notable differences in postoperative pain reduction between the two groups. 15 Patients in Group-2, who received Nasopore packing without an integrated airway, reported lower pain scores compared to Group-1 patients, who received Nasopore packing with an integrated airway. This discrepancy suggests that the presence of the integrated airway may have compromised the softness of the packing material.…”
Section: Discussionmentioning
confidence: 82%
“…Similar results were found in another study, the average SpO 2 (arterial oxyhemoglobin saturation when measured using pulse oximetry) levels were significantly reduced in 33% of the patients that slept with nasal packing without an integrated airway but were within normal limits for all patients with airway integrated nasal packing. 16 Conversely, the other study 15 found that SpO 2 was not significantly different in patients who have undergone septoplasty with nasal packing with and without airway integration.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation